2022
DOI: 10.1038/s41467-021-27807-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the potential effectiveness of earthquake early warning across Europe

Abstract: Here we assess the potential implementation of earthquake early warning (EEW) across Europe, where there is a clear need for measures that mitigate seismic risk. EEW systems consist of seismic networks and mathematical models/algorithms capable of real-time data telemetry that alert stakeholders (e.g., civil-protection authorities, the public) to an earthquake’s nucleation seconds before shaking occurs at target sites. During this time, actions can be taken that might decrease detrimental impacts. We investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Earthquake early warning system makes use of the message carried by the P‐wave arrival to issue warnings about the later coming, and potentially destructive, S and surface waves, to field emergency countermeasures, which are scaled to the different objects to be protected (Allen et al, 2009; Allen & Melgar, 2019; Cremen et al, 2022; Kanamori, 2005; Satriano et al, 2011). If the detection network does not cover the seismic source, it has been shown that SHA may help to improve their performance (Cremen & Galasso, 2020; Zhang, Wu et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Earthquake early warning system makes use of the message carried by the P‐wave arrival to issue warnings about the later coming, and potentially destructive, S and surface waves, to field emergency countermeasures, which are scaled to the different objects to be protected (Allen et al, 2009; Allen & Melgar, 2019; Cremen et al, 2022; Kanamori, 2005; Satriano et al, 2011). If the detection network does not cover the seismic source, it has been shown that SHA may help to improve their performance (Cremen & Galasso, 2020; Zhang, Wu et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…When these seismic waves propagate to the ground, they can induce strong shaking, which causes severe loss of life and damage to the economy. Hence, seismologists monitor earthquakes by recording ground vibrations using seismometers, e.g., to give warnings of seismic activity and minimize the loss (Allen & Stogaitis, 2022;Cremen et al, 2022;Massin et al, 2021;Cremen & Galasso, 2020).…”
Section: Waves and Virtual Realitymentioning
confidence: 99%
“…However, as the EEWS performance is bound to depend on a multitude of uncertain factors, such efforts have, for the most part, understandably targeted individual system characteristics that are more testable, or adopted a narrower scope in their assessment. This usually translates to using proxy targets such as satisfactory alert accuracy (Pinsky, 2017), size of no-alert zones (Kuyuk and Allen, 2013; Picozzi et al, 2015), length of warning times (Böse et al, 2022; Meier et al, 2020), or composite indices combining the above and/or other proxies (Cremen et al, 2022). Many of these studies have, in fact, been instrumental in enhancing particular EEWSs or improving the EEW science in general; yet, they do not provide directly actionable information to decision makers, that is, an assessment of whether EEW can be an effective driver of risk reduction.…”
Section: Introductionmentioning
confidence: 99%